The Potential of Momordica Charantia, Morinda Citrifolia and Centella Asiatica Extracts as Antiobesity Agents - Sahib, Najla Gooda (2009)
The effect of Momordica charantia Extract (MCE), Centella asiatica Extract (CAE) and Morinda citrifolia Fruit Extract (MCFE) on lipoprotein lipase (LPL) activity, pancreatic lipase activity, proliferation and differentiation of 3T3-L1 preadipocytes were investigated to evaluate their potential application for obesity treatment. Dried plant samples were extracted in 99.5% ethanol. Extracts were analyzed for total phenolic compounds and flavonoids utilizing Folin Ciocalteau assay and HPLC respectively. The anti oxidative potential of all extracts were also evaluated using the FRAP and DPPH assays. The inhibitory effects of the extracts on lipoprotein lipase (LPL) and pancreatic lipase (PL) were determined in vitro. The extent of cell proliferation was determined by cell viability assay and the degree of differentiation was measured by Oil Red O staining assay. Results of the study showed that all extracts tested consisted of excellent concentration of phenolics compounds, and catechin and epicatechin was predominantly present in all three extracts. All extracts also showed good anti oxidative potential in scavenging free radicals. At a concentration of 1 mg/mL, the extracts inhibited LPL activity differently, with MCFE showing the highest inhibitory effect (21.4±2.3%), followed by CAE (16.3±1.1 %) and MCE (10.6 ±0.6%). At a concentration of 0.02mg/ml, all three extracts inhibited PL, with CAE showing the highest inhibition (31.1%), followed by MCFE (29.7%) and lastly MCE (21.5 %), with no significance difference. MCE showed the highest inhibitory effect on both cell proliferation and differentiation of preadipocytes. After 72 hours, MCE was found to be most toxic with an LC50 of 1.6mg/L, followed by CAE with an LC50 of 2.4 mg/mL and MCFE had the least cytotoxic effect with LC50 of 4.5 mg/mL. Results after 48 hours of plating showed that MCE exhibited the highest inhibitory effect on differentiation in a dose dependent manner. The highest inhibition, 74.7 ±5.41% of control, occurred at concentration of 0.5 mg/mL. Data from the study indicate that MCE exert potential anti obesity effects by inhibiting proliferation and differentiation of preadipocytes. MCFE can also be used as a therapeutic treatment for obesity due to its relatively high anti LPL and PL activity and low cytotoxic effect.